Complications of Thyroid Surgery & Their Risk Factors: A Prospective Study at a Tertiary Care Center of Eastern Nepal - Panthi, Niranjan; Chettri, S T; Shah, S P; Poudel, D; Manandhar, S; Acharya, K (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Thyroid surgery is one of the commonest surgeries performed by otolaryngologists. Currently, the main postoperative complications are hypocalcemia and recurrent laryngeal nerve (RLN) palsy. Extent of surgery, lack of identification of RLN/ parathyroid glands, malignancy, central compartment neck dissection, lateral neck dissection, previous surgery and size of goiter are the risk factors for complications. The objectives of this study were to determine the frequency of postoperative complications after thyroid surgery and to analyze the risk factors of complications.Methods: It was a prospective study of 45 patients undergoing thyroid surgery in eastern Nepal from March 2014 to September 2015. The postoperative complications and the risk factors associated with these complications were evaluated.Results: There were total of 45 cases of thyroid surgery, with the mean age of 39.04 years. The main postoperative complications were: hypocalcaemia (6 or 13.33% cases) and vocal cord palsy due to recurrent laryngeal nerve injury (5 or 11.11% cases). Temporary hypocalcaemia was observed in 3(6.67%) cases while permanent hypocalcaemia developed in other 3 (6.67%) cases. Similarly, the temporary and permanent recurrent laryngeal nerve palsy occurred in 3 (6.67%) cases and 2 (4.44%)cases respectively. The risk factors associated with hypocalcaemia were: malignancy, repeat operation, central compartment neck dissection and non-identification of parathyroid glands during surgery. Similarly, recurrent laryngeal nerve palsy was observed in cases of malignancy and central compartment neck dissection.Conclusion: The major postoperative complications of thyroid surgery were hypocalcaemia and recurrent laryngeal nerve palsy. Malignancy and central compartment neck dissection had effect on incidence of complications. Sound knowledge of anatomy and meticulous surgical technique are needed to reduce the incidence of complications.